2023
DOI: 10.18240/ijo.2023.01.11
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of success rate and intraocular pressure spikes between selective laser trabeculoplasty and micropulse laser trabeculoplasty in African American and Hispanic patients

Abstract: AIM: To examine the efficacy and safety of micropulse laser trabeculoplasty (MLT) versus selective laser trabeculoplasty (SLT) in a large cohort of primarily African American and Hispanic patients. METHODS: A single center retrospective comparative cohort review conducted at Cook County Health facilities that included patients with a diagnosis of open angle glaucoma or ocular hypertension who received an SLT or MLT procedure between January 2017 and May 2021. RESULTS: Totally 131 eyes of 99 patients were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…[ 37 38 ] Moreover, the safety and efficacy of SLT have been demonstrated across different ethnic groups. [ 15 24 ] This includes Caucasian,[ 39 ] Hispanic,[ 40 ] Brazilian,[ 28 ] Asian,[ 41 ] Indian,[ 42 ] and African[ 43 44 45 ] patients. In studies with mixed ethnicity, Africans have been shown to have a sustained IOP reduction (20.0%) in 90.0% of eyes as compared to 50.0% of Indian eyes at 12 months follow-up.…”
Section: Impact Of Demographics On Outcomesmentioning
confidence: 99%
“…[ 37 38 ] Moreover, the safety and efficacy of SLT have been demonstrated across different ethnic groups. [ 15 24 ] This includes Caucasian,[ 39 ] Hispanic,[ 40 ] Brazilian,[ 28 ] Asian,[ 41 ] Indian,[ 42 ] and African[ 43 44 45 ] patients. In studies with mixed ethnicity, Africans have been shown to have a sustained IOP reduction (20.0%) in 90.0% of eyes as compared to 50.0% of Indian eyes at 12 months follow-up.…”
Section: Impact Of Demographics On Outcomesmentioning
confidence: 99%